Increasing the Accuracy of Recipient Selection for the Smart Indonesia Program (PIP) Using the Moora Method - Heri Gunawan; Ahir Yugo Nugroho; Ria Eka Sari; Adnan Buyung Nst (PT FORMOSA CENDEKIA GLOBAL, 2022)
The selection mechanism of the Smart Indonesia Program (PIP) is very complicated, and the targets or eligibility criteria for Smart Indonesia Program (PIP) participants do not match the accurate data or do not match the reality on the ground, there is still feeling of control in the process which is interpreted as a form of understanding what other people feel and also imagine yourself if you were in that person's position. For this reason, it is necessary to design a desktop-based system using the Microsoft Visual Studio 2010 programming language and created using the Microsoft SQL Server R2 2008 database as the data storage medium, so that if there is an update the system criteria data can be used without having to disassemble it, and data processing runs efficiently and effectively in the system. Decision making on the Moora method is based on criteria and sub-criteria data by considering the total weight of the benefit criteria attributes and the cost attributes of the alternative student data entered into the system, it is known that 6 students have been accepted as potential recipients of education funds through a decision support system , with a decision value.